Exploring Teachers’ Perceptions of Post-Method Pedagogy in ELT - Bhandari, Bhim Lal; Bhandari, Laxman Prasad (International Journal of Language and Literary Studies, 2025)
Post-method pedagogy, introduced by Kumaravadivelu in 1994, emerged as a response to the need for a more effective approach to teaching English that moves beyond the limitations of traditional method-based frameworks. However, most teachers still adopt lectures as the primary method of teaching English in Nepal. This article explores teachers’ perceptions of post-method pedagogy in English Language Teaching (ELT) in Nepal. A phenomenological research design was employed to achieve the purpose of the study. Four community school teachers were purposively selected as the research participants. In-depth interviews were used as a major technique for collecting information from them. This study reveals that teachers hold positive perceptions of this pedagogy that can promote teacher autonomy and quality in English language teaching, and they perceive post-method pedagogy as a way to address the limitations of traditional methods and promote context-sensitive teaching. The study can contribute to teachers constructing context and culture-sensitive pedagogies rather than being imposed by methodological practices.